TEACHING COMMUNICATION AT LESSONS OF ENGLISH THROUGH BUILDING SEL (SOCIAL AND EMOTIONAL LEARNING) SKILLS - Iaburova, Olena (Професіоналізм педагога: теоретичні й методичні аспекти, 2020)
Teaching communication at lessons of English is a vital part of effective lessons of English. Productive communication includes attentive and appreciative listening, clear self-expression as well as main language competences. By practicing communicative skills, students gain a wide range of social skills which are an integral part of expressing opinions, justifying, negotiations, debating, agreeing and disagreeing, making analysis and generalization. The purpose of the article is to generalize foreign strategies in the frame of SEL that gives an opportunity to improve students’ academic outcomes, graduation rates and test scores, makes it easier for students to develop their emotional intelligence, become team-oriented and enhance their leadership skills. The core principles of SEL (Social and Emotional Learning) constitute the practical strategies of teaching communication at the lessons of English though building SEL skills. The author analyzes foreign experience about the impact of enhancing students’ social and emotional learning, effectiveness of school-based universal, social, emotional and behavioral programs, promoting positive youth development through emotional learning interventions in the scientific works of J.A. Durlak. The author defines core factors which are an integral part of SEL implementation, describes a variety of approaches, key elements and strategies which influence students’ communicative skills, eagerness to become active participants of cooperative learning. The author underlines the fact that obtaining emotional vocabulary at lessons of English is essential for both receptive and productive skills of modern students. The ability to differentiate speakers’ emotions, voice tunes, interrogative and negative intonation, reference to the previous events or future perspectives is the skill to be developed by using SEL techniques. One of the strategies, the author describes in the article, is using Emotional and Scenario Cards in the frame of SEL which can be integrated into the process of teaching English aimed at improving students’ communicative skills.